Avaliação dos livros do plano nacional do livro didático (pnld), do ensino fundamental, 1º ao 5º ano: o ensino de geografia e sua relação com a astronomia - Silva, Breno Ferreira da (Universidade Federal do Tocantins, 2022)
The objectiveofthisworkisto make anevaluationofthetextbookofGeography, ofthe Federal ProgramNationalTextbookPlan (PNLD), in theinitial grades ofElementary School (1o to 5oyear), referring to the relations of Geography and Astronomy expressed in the contents of Geography, a book used in 2020 by the Dr. EuvaldoTomaz de Souza Municipal School, in the city of Porto Nacional -Tocantins. The study was carried out, based on the bibliographic evaluation corresponding to the teaching material adopted by that school. The geography collections analyzed in Elementary School, Early Years were: “Crescer Collection”, 1o year – Collection Code 0233P19051 (ALVES et al., 2017) and “AprenderJuntos”, 2o; 3o; 4o; and 5o year - Collection Code 0127P19051 (ALVES et al., 2017) and “AprenderJuntos”, 2o; 3o; 4o; and 5o year - Collection Code 0127P19051 (SILVA, 2017; SILVA, 2017a; SILVA, 2017b; SILVA, 2017c, respectively). The evaluation showed that from 1o to 5oyear of elementary school, the themes studied in Geography books such as periods of the day, orientation/location, weather forecast, climate (weather and climate; climate and vegetation), and Earth movements keep a relationship with Astronomy, since they are related to rotation and translation movements, associated with the tilt of the Earth's axis. It is understood, therefore, that for the satisfactory performance of the geography teacher, in the teaching-learning process, a certain astronomical basis is important to work on these themes.